Differential clinical characteristics and possible predictors of bipolarity in a sample of unipolar and bipolar inpatients. (December 2018) - Serafini, Gianluca; Lamis, Dorian; Canepa, Giovanna; Aguglia, Andrea; Monacelli, Fiammetta; Pardini, Matteo; Pompili, Maurizio; Amore, Mario
Highlights: Major affective disorders are associated with significant psychosocial impairment. Unipolar differ from bipolar inpatients according to specific clinical characteristics. Higher lifetime psychotic symptoms and illness episodes were significant predictors of bipolarity. Abstract: Major affective conditions including both unipolar (UD) and bipolar disorders (BD) are associated with significant disability throughout the life course. We aimed to investigate the most relevant socio-demographic/clinical differences between UD and BD subjects. Our sample included 180 inpatients, of which 82 (45.5%) participants were diagnosed with UD and 98 (54.5%) with BD. Relative to UD patients, BD individuals were more likely to report prior psychoactive medications, lifetime psychotic symptoms, nicotine abuse, a reduced ability to provide to their needs, gambling behavior, and fewer nonsuicidal self-harm episodes. Moreover, BD patients were more likely to report severe side effects related to medications, a younger age at illness onset and first hospitalization, higher illness episodes, and longer illness duration in years than UD subjects. In a multivariate logistic analysis accounting for age, gender, and socio-demographic characteristics, a significant positive contribution to bipolarity was found only for higher lifetime psychotic symptoms (β = 1.178; p ≤ .05) and number of illness episodes (β = .155; p ≤ .05). The present findings suggest that specific clinical factors may be used in order to better distinguish between UD and BD subgroups. Further studies are required to replicate these findings in larger samples.